Efficacy of rituximab for glandular Sjö gren's disease according to international clinical trials - A. V. Torgashina (Современная ревматология)
Sjögren's disease (SD) is a chronic autoimmune disease characterized by lymphoplasmacytic infiltration of the exocrine glands, leading to the development of their destruction and progressive functional failure. The prevalence of SD is about 5%, which makes it one of the most common autoimmune diseases. SD often has a chronic, slowly progressing course.The paper discusses the results of international clinical trials of the efficiency of anti-B-cell therapy with rituximab (RTM) for glandular SD. It considers the impact of this therapy on various immunological, histological indicators, subjective and objective parameters of glandular function, and disease activity. Possible reasons for the discrepancy between the results of open-label clinical trials and randomized clinical trials, as well as predictors for the efficiency of RTM therapy are discussed.It has been found that RTM used to treat SD effectively reduces B-cell activity, improves the morphological pattern in the salivary glands and some extraglandular manifestations of the disease, and diminishes dryness and weakness. Anti-B-cell drugs have a great potential to treat SD.